Oxidative stress and outcome of antioxidant supplementation in patients with polycystic ovarian syndrome (PCOS) - Panti, Abubakar A.; Shehu, Constance E.; Saidu, Yusuf; Tunau, Karima A.; Nwobodo, Emmanuel I.; Jimoh, Abdulgafar; Bilbis, Lawal S.; Umar, Atteque B.; Hassan, Mairo (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: PCOS is a condition with significant decrease in antioxidant with an increased risk of oxidative stress. Antioxidant supplementation has been shown to improve insulin sensitivity in PCOS and may improve outcome of management of PCOS. Objectives of this study were to determine the oxidative stress level of PCOS patients, to assess the effect of antioxidant supplementation on the outcome of management of PCOS and to compare with a control group. Methods: The study was a single blind randomised control trial involving 200 patients with PCOS. The study was conducted at Usmanu Danfodiyo University Teaching Hospital Sokoto. They were randomly divided into intervention and control groups and base line serum levels of oxidative stress marker, antioxidant enzymes, vitamins and minerals were determined. Antioxidant supplementation and placebo were given to the intervention and control groups respectively. All the patients had ovulation induction with clomiphene citrate and were followed up for 6 months. Outcome measures were clinical pregnancy or menstrual regularisation. Level of significance was <0.05. Results: There was statistical significance in the serum levels of oxidative stress marker, antioxidant enzymes, vitamins and minerals between the two groups (post intervention). Glutathione peroxidase (p = 0.001), superoxide dismutase (p = 0.0001), catalase (p= 0.0369), melondialdehyde (p= 0.007), Vitamin A, Vitamin C, Vitamin E (p = 0.0001), zinc and copper (p = 0.0001). The clinical pregnancy outcomes were 22 (22%) versus 2 (2%); live births 18 (18%) versus 2 (2%) and menstrual regularisation 48 (48%) versus 46 (46%) in the intervention and control groups respectively. Conclusions: Antioxidant supplementation in this study significantly affected pregnancy rate in patients with PCOS. Larger studies are suggested to revisit the conclusion of the Cochrane review that antioxidants supplementation had no significant role in female infertility.